Tried by war : Abraham Lincoln as commander in chief - McPherson, James M. (New York : Penguin Press, 2008)
Evaluates Lincoln's talents as a commander in chief in spite of limited military experience, tracing the ways in which he worked with, or against, his senior commanders to defeat the Confederacy and reshape the presidential role.
The quest for a strategy, 1861 -- The bottom is out of the tub -- You must act -- A question of legs -- Destroy the rebel army, if possible -- The promise must now be kept -- Lee's army, and not Richmond, is your true objective point -- The heaviest blow yet dealt to the rebellion -- If it takes three years more -- No peace without victory.
Includes bibliographical references (pages 273-314) and index.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Military leadership; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; Executive power -- United States -- History -- 19th century; Presidents -- United States -- Biography; Whitman College -- Memorial bookplates -- Class of 1936.; Amerikaanse burgeroorlog; Militaire bevelhebbers; Militaire strategie; Verenigde Staten; Lincoln, Abraham; 2; Sezessionskrieg (1861-1865); Sezessionskrieg -- (1861-1865); Lincoln, Abraham, -- 1809-1865.; 0; Sezessionskrieg; Lincoln, Abraham, -- 1809-1865.; Executive power; Military leadership; Political science; Presidents; United States; 1800 - 1899; Biography; History